1991
DOI: 10.1128/aac.35.2.394
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of selected antiviral compounds on human hepatitis B virus DNA synthesis

Abstract: By using an assay system based on a human hepatoblastoma cell line (HB611) that continuously synthesizes hepatitis B virus DNA, the following compounds were found to inhibit hepatitis B virus DNA synthesis at concentrations that were significantly lower than their minimum cytotoxic concentrations: 9-(2-phosphonylmethoxyethyl)-2,6-dianiinopurine (PMEDAP), (S)-9-(3-hydroxy-2-phosphonylmethoxypropyl)adenine, 9-(phosphonylmethoxyethyl)adenine, 2',3'-dideoxy-2',3'-didehydrocytidine, and 2',3'-dideoxycytidine. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
48
1
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 14 publications
5
48
1
1
Order By: Relevance
“…However, the EC50 values that we obtained for PMEG and PMEGEE were much lower than those obtained by others, and the EC50 value of PMPA was higher than that of the Southern blot analysis (18). The selective indexes of (S)-HPMPC and araA estimated by this assay system were higher than previous results (17,18). However, these differences should pose no problem in the screening of anti-HBV compounds.…”
Section: Resultscontrasting
confidence: 53%
See 3 more Smart Citations
“…However, the EC50 values that we obtained for PMEG and PMEGEE were much lower than those obtained by others, and the EC50 value of PMPA was higher than that of the Southern blot analysis (18). The selective indexes of (S)-HPMPC and araA estimated by this assay system were higher than previous results (17,18). However, these differences should pose no problem in the screening of anti-HBV compounds.…”
Section: Resultscontrasting
confidence: 53%
“…Yokota et al (17,18) was also similar to previously reported data (18). However, the EC50 values that we obtained for PMEG and PMEGEE were much lower than those obtained by others, and the EC50 value of PMPA was higher than that of the Southern blot analysis (18).…”
Section: Resultssupporting
confidence: 50%
See 2 more Smart Citations
“…Addressing these questions will open new perspectives for the clinical usefulness of these nucleotide analogues, thereby pertaining to the importance (or "magic") of the phosphonate bound. 7 therefore, does not exist of (R)-and (S)-enantiomers, were first mentioned by De Clercq et al [1]. From a mechanistic viewpoint, all acyclic nucleoside phosphonates (ANPs) need two consecutive intracellular phosphorylations, to their diphosphate form, before they can interact with their target enzyme (DNA polymerase for DNA viruses, reverse transcriptase for retroviruses) as alternate substrates (with respect to dATP, for PMEA diphosphate or (S)-…”
Section: Introductionmentioning
confidence: 99%